Simulation-based summative assessment in healthcare: an overview of key principles for practice - Clément Buléon; Laurent Mattatia; Rebecca D. Minehart; Jenny W. Rudolph; Fernande J. Lois; Erwan Guillouet; Anne-Laure Philippon; Olivier Brissaud; Antoine Lefevre-Scelles; Dan Benhamou; François Lecomte; the SoFraSimS Assessment with simulation group; et al. (Advances in Simulation, 2022)
Abstract Background Healthcare curricula need summative assessments relevant to and representative of clinical situations to best select and train learners. Simulation provides multiple benefits with a growing literature base proving its utility for training in a formative context. Advancing to the next step, “the use of simulation for summative assessment” requires rigorous and evidence-based development because any summative assessment is high stakes for participants, trainers, and programs. The first step of this process is to identify the baseline from which we can start. Methods First, using a modified nominal group technique, a task force of 34 panelists defined topics to clarify the why, how, what, when, and who for using simulation-based summative assessment (SBSA). Second, each topic was explored by a group of panelists based on state-of-the-art literature reviews technique with a snowball method to identify further references. Our goal was to identify current knowledge and potential recommendations for future directions. Results were cross-checked among groups and reviewed by an independent expert committee. Results Seven topics were selected by the task force: “What can be assessed in simulation?”, “Assessment tools for SBSA”, “Consequences of undergoing the SBSA process”, “Scenarios for SBSA”, “Debriefing, video, and research for SBSA”, “Trainers for SBSA”, and “Implementation of SBSA in healthcare”. Together, these seven explorations provide an overview of what is known and can be done with relative certainty, and what is unknown and probably needs further investigation. Based on this work, we highlighted the trustworthiness of different summative assessment-related conclusions, the remaining important problems and questions, and their consequences for participants and institutions of how SBSA is conducted. Conclusion Our results identified among the seven topics one area with robust evidence in the literature (“What can be assessed in simulation?”), three areas with evidence that require guidance by expert opinion (“Assessment tools for SBSA”, “Scenarios for SBSA”, “Implementation of SBSA in healthcare”), and three areas with weak or emerging evidence (“Consequences of undergoing the SBSA process”, “Debriefing for SBSA”, “Trainers for SBSA”). Using SBSA holds much promise, with increasing demand for this application. Due to the important stakes involved, it must be rigorously conducted and supervised. Guidelines for good practice should be formalized to help with conduct and implementation. We believe this baseline can direct future investigation and the development of guidelines.